Greening the economy - Steven Poelhekke (Tinbergen Institute, 2024)
The economy is traditionally human-centered and has given too little consideration to plants, animals, climate, and nature in general. What should the economy do to become 'green'? Changing people's social norms would be ideal but is hard to achieve. Second best is to regulate and constrain the economy through taxes, subsidies, standards, and redistribution. However, setting these to the 'right' level is challenging and must address how much humans care about nature, the desire to retain the benefits of economic growth, and the political feasibility of implementing national and international policies that accelerate the transition to a green economy.
Keywords: 330; green economy; climate change; social norms; climate policy; redistribution